The effect of intrapartum prolonged oxygen exposure on fetal metabolic status: secondary analysis from a randomized controlled trial - Chuai, Fang; Dong, Tong; Liu, Yuan; Jiang, Wen; Zhang, Lanmei; Chen, Lei; Chuai, Yunhai; Zhou, Yuhang (Frontiers in Endocrinology, 2023)
Objective: To assess the effect of maternal prolonged oxygen exposure during labor on fetal acid-base status, fetal heart rate tracings, and umbilical cord arterial metabolites. Design: A secondary analysis. Setting(s): Three tertiary teaching hospitals in Beijing, China. Participants: About 140 women in the latent phase of labor with no complications. Intervention: Participants were randomly allocated in a 1:1 ratio to receive either 10 L of oxygen per minute by tight-fitting simple facemask until delivery, or room air only. Main outcome measures: Primary outcome was the umbilical cord arterial lactate. Results: Baseline demographics and labor outcomes were similar between oxygen and room air groups, the time from randomization to delivery was 322 ± 147 minutes. There were no differences between the two groups in the umbilical cord arterial lactate (mean difference 0.3 mmol/L, 95% confidence interval -0.2 to 0.9), the number of participants with high risk category II fetal heart rate tracings (relative risk 0.94, 95% confidence interval 0.68 to 1.32), or the duration of those high risk tracings (mean difference 3.6 minutes, 95% confidence interval -9.3 to 16.4). Prolonged oxygen exposure significantly altered 91 umbilical cord arterial metabolites, and these alterations did not appear to be related to oxidative stress. Conclusions: Maternal prolonged oxygen exposure during labor did not affect either the umbilical cord arterial lactate or high risk category II fetal heart rate tracings, but might result in alterations of the umbilical cord arterial metabolic profile.